IMPLEMENTASI PELAYANAN PRIMA PADA NASABAH BANK SYARIAH MANDIRI CABANG BENGKALIS - Rahim Rahim; Dwi Astuti; Teguh Widodo (Politeknik Negeri Bengkalis, 2016)
Abstract: The present research was conducted atBank Syariah Mandiri of Bengkalis Branch. The purposes of this research are to know the implementation of the excellent service for Bank Syariah Mandiriof Bengkalis Branch’s customer, and to know what kind of services that have been implemented for their customer. The kind of research isthe description research.The result of the research showed thatis the Bank Syariah Mandiri of Bengkalis Branchhave implemented the excellent service to the customer according the standards that assigned by Bank Syariah Mandiri of Bengkalis Branch. Keywords: Service Excellent, Customer, Bank